Near-complete whole-genome sequencing of two burkholderia pseudomallei strains harbouring novel molecular class D beta-lactamase genes, isolated from Malaysia - Zainulabid, Ummu Afeera; Mohamad Zain, Norirwanisyam; Arumugam, Janaki; Kamarudin, Norhidayah; Zainal Abidin, Muhammad Adil; Mokti, Abdullah Shamshir Abd; Nordin, Noorlina; Rakawi, Ahmad Faizal; Majid, Aman Shah Abdul; Ashok, Gnanasekaran; Francis, Alex Lourdes; Tay, Darren Dean; et al. (American Society for Microbiology, 2022)
Here, we present two 7.1- and 7.3-bp near-complete genome sequences of Burkholderia pseudomallei strains of HTAA077 and HRPB058, isolated from a pus culture from a confirmed melioidosis patient at Hospital Tengku Ampuan Afzan, Kuantan, Malaysia, and from blood culture from a patient at Hospital Raja Permaisuri Bainun, Ipoh, Malaysia, using a Nanopore MinION instrument.